2018
DOI: 10.24854/jps.v5i2.500
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan antara Mindfulness dengan Depresi pada Remaja

Abstract: Depresi merupakan gangguan mental yang umum terjadi di dunia, namun tetap menjadi suatu faktor kontribusi pada penurunan kecepatan penyembuhan berbagai penyakit lain. Prevalensi gangguan depresif mayor merupakan salah satu yang tertinggi dan angka tersebut terus meningkat sepanjang sepuluh tahun belakangan ini. Beberapa faktor yang berperan terhadap penurunan depresi banyak dilakukan. Salah satu penelitian di Amerika menunjukkan bahwa individu yang mengalami depresi atau simtom depresi cenderung memiliki tingk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 12 publications
1
4
0
8
Order By: Relevance
“…In this regards, the more adolescents with divorced parents can accept the positive and negative experiences as person coming from divorced family, they will feel less depressed. Supporting another finding among Indonesian community adolescents that found negative correlation between mindfulness and depression [17], this current study suggests that even among adolescents with significant stressful live events, mindfulness bring positive impact on their depression level. Therefore, it can be concluded that trait of mindfulness seems can be potential protective factors from depression, not only among normative adolescent population, but also for vulnerable population, such as they are with parental divorce.…”
Section: B Correlation Of Depression and Mindfulnesssupporting
confidence: 85%
See 1 more Smart Citation
“…In this regards, the more adolescents with divorced parents can accept the positive and negative experiences as person coming from divorced family, they will feel less depressed. Supporting another finding among Indonesian community adolescents that found negative correlation between mindfulness and depression [17], this current study suggests that even among adolescents with significant stressful live events, mindfulness bring positive impact on their depression level. Therefore, it can be concluded that trait of mindfulness seems can be potential protective factors from depression, not only among normative adolescent population, but also for vulnerable population, such as they are with parental divorce.…”
Section: B Correlation Of Depression and Mindfulnesssupporting
confidence: 85%
“…Some previous research has shown a negative relationship between mindfulness and depression in the community sample of adolescents. In this regards, research found that when adolescents becomes more aware and accept various thoughts and feelings, they will tend to have lower symptoms of depression [17]. However, to what extent mindfulness is also associated with depression in adolescents with divorced parents still needs further investigation.…”
Section: Introductionmentioning
confidence: 98%
“…Naicker, Galambos, Zeng, Senthilselvan, & Colman (2013), depresi merupakan gangguan mental yang lazim ditemui pada individu di bawah 18 tahun sekitar 8% -20%. Fourianalistyawati & Listiyandini (2017), melakukan penelitian cross sectional pada remaja di salah satu SMA Malang, Jawa Timur, mendapati 32,5% depresi ringan, 28,2% depresi moderat dan 11,1% depresi berat.…”
Section: Latar Belakangunclassified
“…Menurut penelitian terdapat hubungan yang negatif dan sangat signifikan antara mindfulness dan depresi. Khususnya pada aspek acting with awareness dan non judging of inner experience (Fourianalistyawati & Listiyandini , 2017). Acting with awareness adalah kemampuan mempertahankan kesadaran dalam kegiatan rutin dibandingkan dengan bertindak secara otomatis, selain itu non judging of inner experience adalah suatu kemampuan untuk menjauh dari pikiran untuk mengevaluasi sensasi, kognisi, dan emosi diri (Baer, 2016).…”
Section: Mindfulnessunclassified
“…Acting with awareness adalah kemampuan mempertahankan kesadaran dalam kegiatan rutin dibandingkan dengan bertindak secara otomatis, selain itu non judging of inner experience adalah suatu kemampuan untuk menjauh dari pikiran untuk mengevaluasi sensasi, kognisi, dan emosi diri (Baer, 2016). Dengan demikian dapat dikatakan jika tingkat mindfulness tinggi maka tingkat depresi yang dialami semakin rendah (Fourianalistyawati & Listiyandini , 2017).…”
Section: Mindfulnessunclassified